2012
DOI: 10.1177/120347541201600510
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions and Attitudes Toward Vitiligo

Abstract: Various misconceptions and negative attitudes about vitiligo among the public are prevalent. Educating the public about vitiligo could ultimately lead to better psychosocial well-being of vitiligo patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 10 publications
1
29
0
Order By: Relevance
“…The study from Saudi Arabia had reported that 56.1% of their subjects were unwilling for the same. [ 10 ] Only about one-third of the participants in this study were agreeable for marriage relations with a family having a vitiligo patient.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The study from Saudi Arabia had reported that 56.1% of their subjects were unwilling for the same. [ 10 ] Only about one-third of the participants in this study were agreeable for marriage relations with a family having a vitiligo patient.…”
Section: Discussionmentioning
confidence: 89%
“…There is no Indian study available with which these data could be compared, however, one recent study from Saudi Arabia has focused on public perceptions and attitudes toward vitiligo patients. [ 10 ] The causes assumed by the participants in that study included autoimmunity (41.2%), heredity (40.50%), diet (30.50%), poor hygiene (22.5%), and evil eye (29.3%). The notion of contagiousness was maintained by less number (8.0%) of the participants in that study as compared to ours (17.0%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Saudi Arabia, patients with vitiligo are often perceived as contagious (33.1%). 25 In British South Asian societies, patients not only faced rejection from family and society but in many cases experienced detachment from their ethnicity as well. Many patients have developed a “spoiled identity”, or ruined and weakened sense of identity, to internalize the isolation and stigmatization they have endured.…”
Section: Resultsmentioning
confidence: 99%
“…If the percentage of repigmentation is clinically estimated, the bias of subjective assessment without objective measurements leads to incorrect evaluations . The techniques available for vitiligo assessment are either subjective, semi‐objective, or objective methods …”
Section: Introductionmentioning
confidence: 99%